POSITIVISASI” HUKUM ISLAM DALAM UNDANG-UNDANG PERBANKAN SYARIAH DI INDONESIA - Zuliansyah, Ahmad (Universitas Islam Negeri Raden Intan Lampung, 2011)
Abstak: The application of Islamic law in the activities of banking / finance or other modern economic activities is not a simple job. The study of the banking law, or sharia financesharia law to be an interesting study and challenging for the world of law in Indonesia where the positive law (law) in the country of Indonesia is different from that applicableto the religious law (Islam). Enforcement of religious law (Islam) must go through a process referred to as the